Development and validation of simple simultaneous analysis for amlodipine and glibenclamide by nonderivatization high-performance liquid chromatography-fluorescence - Febrina Amelia Saputri; Anisahtul Alawiyah; Ayu Brilliany Firsty; Sandra Megantara; Arif Satria Wira Kusuma; Taofik Rusdiana; Aliya Nur Hasanah; Mutakin Mutakin; Ingrid S Surono; Rizky Abdulah (Wolters Kluwer Medknow Publications, 2018)
Studies have shown that about 65% of diabetics have hypertension. Treatment for diabetic patients with hypertension is usually given a combination of drugs such as amlodipine (AML) and glibenclamide (GLI). The aim of this study was to develop and validate the simple simultaneous analysis method for separation of AML and GLI using high-performance liquid chromatography (HPLC) with fluorescence detector without derivatization. The arrangement of isocratic and gradient methods, mobile phase compositions, and flow rates to develop and validate the simple simultaneous analysis method for separation of AML and GLI by nonderivatization HPLC fluorescence was done. Optimum condition was obtained using an RP 18 (125 mm × 4 mm, i.d., 5 μm) and guard column RP 18 (4 mm × 4 mm, i.d., 5 μm) with mobile phase composition containing acetonitrile and phosphate buffer pH 3.0 using a 20:80 gradient condition at flow rate 1.0 ml/min measured at 361 nm for λ excitation and 442 nm for λ emission for AML and 235 nm for λ excitation and 354 nm for λ emission for GLI. The analysis of AML and GLI demonstrated a valid result with r2 value 0.999, recoveries were 100.04% and 99.14% relative standard deviations were 0.508% and 0,797%, respectively, detection limits were 0.055 and 0.104 μg/ml, and quantification limits were 0.166 and 0.316 μg/ml, respectively. An accurate method of separation for AML and GLI using HPLC with fluorescence detector without derivatization has been validated.